Synthesis and Characterization of Novel Biopolyesters from Suberin and Model Comonomers - Sousa, Andreia F.
The synthesis of novel polyesters from model long-chain aliphatic monomers and from suberin reactive aliphatic fragments was conducted using mild polycondensation or polytransesterification conditions. The ensuing polyesters were characterized by means of various techniques. When mixtures of simple suberin-like monomers were used, the ensuing polyesters had very regular structures, with melting temperatures around 80 degrees C and glass transitions below room temperature. This first systematic study of the exploitation of suberin as a precursor to novel aliphatic polyesters confirmed the huge potential of using this abundant renewable resource to prepare macromolecular materials for promising applications.